Thailand Policies for PM 2.5 and the Hidden Problems - Wongtongtair, Supim (GHMJ (Global Health Management Journal), 2025)
The PM 2.5 pollution problem in Thailand is intensifying in major cities and across the country, significantly impacting public health. According to surveys in Thailand, PM 2.5 originates from three primary factors: automobiles, outdoor biomass burning/factories, and the inversion phenomenon or stagnant air conditions. Although Thailand has implemented policies to address these three key causes, their practical execution has fallen short of achieving the desired outcomes. A deeper analysis reveals hidden problems within these policies, which hinder their effectiveness. This presentation aims to highlight these hidden issues and propose preliminary solutions to mitigate them, thereby contributing to more successful PM 2.5 management in the future. Published: 08 February 2025.